In vitro and in vivo activity of R- and S- praziquantel enantiomers and the main human metabolite trans-4-hydroxy-praziquantel against Schistosoma haematobium - Kovač, Jana (Parasit Vectors, 2017)
BACKGROUND: Praziquantel (PZQ) is the mainstay of schistosomiasis control and has been successfully used for decades. However, its mechanism of action is not fully understood. While the majority of studies have been conducted on Schistosoma mansoni, it is not known which enantiomer, R- or S-praziquantel (R-/S-PZQ), is responsible for the activity on Schistosoma haematobium. METHODS: In vitro and in vivo studies were conducted to evaluate the activity of R- and S-PZQ, racemic PZQ and the main human metabolite, namely trans-4-OH-PZQ, on S. haematobium. IC(50) values on adult S. haematobium were determined in vitro. Dose-response relationship studies were performed in golden Syrian hamsters, harbouring a chronic S. haematobium infection. RESULTS: R-PZQ displayed the highest activity against adult worms in vitro, revealing an IC(50) of 0.007 μg/ml at 4 h and 0.01 μg/ml at 72 h. In contrast, S-PZQ was 501× less active (eudysmic ratio at 4 h), with an IC(50) of 3.51 and 3.40 μg/ml (4 and 72 h, respectively). Racemic PZQ and trans-4-OH-PZQ resulted in an IC(50) of 0.03 μg/ml and 1.47 μg/ml both at 4 and 72 h, respectively. In vivo, R-PZQ was the most potent drug with worm burden reductions (WBRs) of 98.5, 75.6 and 73.3% at 125.0, 62.5 and 31.0 mg/kg, respectively. A single oral dose of 250.0 mg/kg PZQ resulted in a WBR of 99.3%. S-PZQ was highly active in vivo at 250.0 and 500.0 mg/kg with WBRs of 83.0 and 94.1%, respectively. The lowest tested dose of S-PZQ, 125.0 mg/kg, showed moderate activity (WBR of 46.7%). The calculated ED(50) for R- and S-PZQ were 24.7 and 127.6 mg/kg, respectively, with a corresponding eudysmic ratio of 5.17. CONCLUSION: Our data support the theory of R-PZQ driving the antischistosomal activity. Interestingly, also S-PZQ proved to possess a significant activity towards S. haematobium, particularly in vivo.